Actividad. (UNED, 2023)
De izquierda a derecha al frente, se presentan María Elena Azofeifa Salazar, Mayra Noguera Paz, Grace Alfaro Alpízar, Sherman Thomas Jackson, Maritza Esquivel Chinchilla (Al fondo junto a la pizarra)